Ketersediaan Fosfor pada Tanah Andisol untuk Jagung (Zea maysL.) oleh Inokulum Bakteri Pelarut Fosfat - Tamad, ,; Ma’as, Azwar; Radjagukguk, Bostang; Hanudin, Eko; Widada, Jaka (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Andisols has relatively low phosphorus availability due to its adsorption by allophane. Phosphate solubilizing bacteria (PSB) increases the availability of P via release of adsorpted-P. The aims of this research were to determine: 1) anorganicP solubilization, 2) organic-P mineralization, 3) blocking of Andisols adsorption site, and 4) effective PSB inoculant. The research was arranged in completely randomized design, with PSB inoculant as treatment. Variables observed were solubleP, mineralize-P, adsorpted-P, pH, total acidity, PSB population, phosphatase and phythase activity, relative surface charge, and maize’s growth component. The result showed that PSB inoculation increased soluble-P from 30 to between 150 and 195 ppm P, increased mineralize-P from 23.7 to between 63.6 and 91.7 ppm P, and decreased P-adsorption from 95 to between 36 and 13%. PSB inoculation decreased the Andisols pH, increased the total acidity, PSB population, the phosphatase and phytase activity, and PSB had relatively high of relative surface charge (69%). The PSB inoculation increased maize P absorption in the range of 70 and 75 mg P plant-1, and increased relative agronomic effectiveness (RAE )between 145 and 150%. Liquid and solid PSB inoculant had no different effect in increasing maize growth. Keywords: Andisol, P release, phosphate solubilizing bacteria, phosphatase, phytase